Moral Hazard in Health Insurance: What We Know and How We Know It. Issue 4 (3rd May 2018) - Einav, Liran; Finkelstein, Amy
Abstract: We describe research on the impact of health insurance on healthcare spending ("moral hazard"), and use this context to illustrate the value of and important complementarities between different empirical approaches. One common approach is to emphasize a credible research design; we review results from two randomized experiments, as well as some quasi-experimental studies. This work has produced compelling evidence that moral hazard in health insurance exists—that is, individuals, on average, consume less healthcare when they are required to pay more for it out of pocket—as well as qualitative evidence about its nature. These studies alone, however, provide little guidance for forecasting healthcare spending under contracts not directly observed in the data. Therefore, a second and complementary approach is to develop an economic model that can be used out of sample. We note that modeling choices can be consequential: different economic models may fit the reduced form but deliver different counterfactual predictions. An additional role of the more descriptive analyses is therefore to provide guidance regarding model choice.